The effects of chronic low dose organic arsenic exposure on the kidney : mechanism of injury and microscopic changes - Wan Muhamad Salahudin Wan Salleh (Kulliyyah of Medicine, International Islamic University Malaysia, 2021)
Chronic exposure to inorganic arsenic has been linked with multiple medical conditions, which shifted the use of inorganic to the organic-based herbicide, monosodium methyl arsenate (MSMA). However, with increasing numbers of chronic kidney disease of unknown causes (CKDu), chronic exposure to herbicide is believed to be one of the potential explanation. To date, studies on the effects of organic arsenic exposure on the kidney are limited. Therefore, this study aimed to investigate the effect of chronic oral organic arsenic exposure on the rat's kidney. Thirty-six Sprague Dawley rats (N=36) were randomly divided into MSMA exposed, and its corresponding control groups for 2-,4- and 6-month, each with six animals per group. The exposed groups were given oral MSMA at 63.20 mg/kg body weight, while control groups received distilled water. At the end of each duration, the serum was collected for the creatinine level. The kidney tissues were harvested for arsenic level measurement, histopathological, immunohistochemistry, real-time PCR analysis and ultrastructural analysis. Genes expressions were done for kidney injury marker gene (KIM-1), oxidative stress genes (Catalase, GSR, NOS1), apoptosis genes (Tp53, Caspase-3 and Caspase-9) and inflammatory genes (Interleukin-6 and Interleukin-8). Serum creatinine was not significantly different between exposed and control groups. Tissue arsenic level was significantly higher in exposed groups as compared to that of the control group. All gene expression markers were downregulated at 2-month and upregulated at 4-month except for Catalase which remained downregulated. At 6-month, only KIM-1, GSR and Caspase-3 remained upregulated. Histological, immunohistochemistry and ultrastructural findings showed chronological changes in the glomeruli and proximal tubules with increased expressions of malondialdehyde (MDA) staining, Caspase-3 and TUNEL staining with the duration of exposure. Therefore, chronic oral exposure to low dose organic arsenic has demonstrated evidence of kidney injury in rats possibly due to oxidative stress.